Cerebral protection devices for transcatheter aortic valve replacement. (3rd July 2017) - Jobanputra, Yash; Jones, Brandon M; Mohananey, Divyanshu; Fatima, Benish; Kandregula, Krishna; Kapadia, Samir R.
ABSTRACT: Introduction : Stroke is a devastating, potential complication of any cardiovascular procedure including transcatheter aortic valve implantation (TAVI). Even clinically silent lesions as detected by magnetic resonance imaging have been associated with poor long-term cognitive outcomes. As a result, extensive efforts have been focused on developing stroke preventative strategies including the development of novel embolic protection devices. These devices aim to reduce this risk by capturing or deflecting emboli away from the cerebral circulation. Areas covered : This review provides an insight into the incidence and mechanisms of neurologic events during TAVI, explores the design features and initial human experience of each of the cerebral embolic protection devices that have been used during TAVI, and carefully explains the major clinical trials of each of these devices with a focus on safety, efficacy and other reported outcomes. Expert commentary : The potential benefit of neuroprotection cannot be ignored as TAVI widens its scope to include younger and lower-risk patients wherein preventing a procedure related cerebral injury would potentially prevent long-term morbidity and mortality.